Starvation and pseudo-starvation as drivers of cancer metastasis through translation reprogramming - Garcia-Jimenez, C; Goding, C (Elsevier, 2018)
Considerable progress has been made in identifying microenvironmental signals that effect the reversible phenotypic transitions underpinning the early steps in the metastatic cascade. However, although the general principles underlying metastatic dissemination have been broadly outlined, a common theme that unifies many of the triggers of invasive behavior in tumors has yet to emerge. Here we discuss how many diverse signals that induce invasion converge on the reprogramming of protein translation via phosphorylation of eIF2α, a hallmark of the starvation response. These include starvation as a consequence of nutrient or oxygen limitation, or pseudo-starvation imposed by cell-extrinsic microenvironmental signals or by cell-intrinsic events, including oncogene activation. Since in response to resource limitation single-cell organisms undergo phenotypic transitions remarkably similar to those observed within tumors, we propose that a starvation/pseudo-starvation model to explain cancer progression provides an integrated and evolutionarily conserved conceptual framework to understand the progression of this complex disease.